FnS: Enhancing Traffic Mobility and Public Safety based on a Hybrid Transportation System - Souza, Allan M. de; Botega, Leonardo C. [UNESP]; Villas, Leandro; IEEE (Ieee, 2018)
Recently, many cities are facing mobility and safety issues, commonly related to traffic congestion and the high number of city-wide criminal incidents. Several Intelligent Transportation Systems (ITS) were proposed to overcome mobility issues. Meanwhile, some safety-based systems were proposed to guide pedestrians and drivers toward safest paths. However, most of these systems address only a single issue. Hence, in order to avoid traffic congestion, an ITS may guide vehicles toward risky areas, while a safety-based system may guide them toward congested ones, focusing only on the safety of drivers and passengers. This paper introduces FnS (Faster and Safer), a hybrid ITS which employs accurate knowledge about traffic conditions and unsafety levels on roads for improving the safety of drivers and passengers at the same time it deals with traffic congestion. Simulation results under a realistic scenario have shown that FnS outperformed state-of-the-art approaches that deal with mobility or safety issues.